1989
DOI: 10.1093/intimm/1.2.205
|View full text |Cite
|
Sign up to set email alerts
|

A novel membrane glycoprotein capable of inhibiting membrane attack by homologous complement

Abstract: Neuraminidase-treated human erythrocytes become sensitive to haemolysis by heterologous serum via activation of the alternative complement pathway (ACP), while remaining insensitive to homologous serum because of the presence of inhibitors on the cell membrane. We obtained a monoclonal antibody which renders the neuraminidase-treated erythrocytes sensitive to haemolysis by homologous human serum via the ACP. This antibody reacts with a 20 KDa membrane glycoprotein which interferes with the terminal stage of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
108
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 183 publications
(113 citation statements)
references
References 0 publications
5
108
0
Order By: Relevance
“…This covered all the Thr (10,13,29) and Ser (20,21) residues, which are potential O-glycosylation sites, in the first half of the CD59 molecule. The data that were obtained were identical to the published amino acid sequence (45,46). The repetitive yields for the five residues at potential sites for O-glycosylation were close to the predicted value (data not included).…”
Section: Characterization Of the O-glycans Attached To Humansupporting
confidence: 69%
“…This covered all the Thr (10,13,29) and Ser (20,21) residues, which are potential O-glycosylation sites, in the first half of the CD59 molecule. The data that were obtained were identical to the published amino acid sequence (45,46). The repetitive yields for the five residues at potential sites for O-glycosylation were close to the predicted value (data not included).…”
Section: Characterization Of the O-glycans Attached To Humansupporting
confidence: 69%
“…Three cell-associated regulators function intrinsically on the surface membranes of self cells for this purpose. In humans, these intrinsic regulators consist of DAF (Medof et al, 1984), membrane cofactor protein (CD46) (Seya et al, 1986), and CD59 (Davies et al, 1989;Holguin et al, 1989;Okada et al, 1989), all three of which are ubiquitously expressed on almost all cell types. In the mouse, DAF and CD59 are widely distributed on virtually all cells as in humans, whereas membrane cofactor protein is expressed significantly only in the testis.…”
Section: Discussionmentioning
confidence: 99%
“…Their and our experiments on CDC were performed with animal complement instead of human complement. Since human cells bear membrane proteins which inhibit attack by human complement (Okada et al, 1989), the CDC observed in vitro may not occur in the human body.…”
Section: Discussionmentioning
confidence: 99%